Application of Manure Rather Than Plant-Origin Organic Fertilizers Alters the Fungal Community in Continuous Cropping Tobacco Soil - Yan Su; Yan Su; Haiyun Zi; Xiaomeng Wei; Binbin Hu; Xiaopeng Deng; Yi Chen; Yonglei Jiang (Frontiers in Microbiology, 2022)
Continuous cropping leads to the development of serious fungal diseases in tobacco plants and depleted yield of tobacco (Nicotiana tabacum), which can be mitigated by organic fertilization. Yet, we know little about how organic fertilizers affect the fungal community of continuous cropping tobacco soil. In this study, we investigated the soil fungal community after 11 years of tobacco planting with chemical fertilization (CF) or chemical fertilization combined with organic fertilizers obtained from plant or animal origin, including oil cake (CFO), straw (CFS), and farmyard fertilizer (CFM). The predominant phyla of Ascomycota (70%) and Mortierellomycota (15%) were identified in all the treatments. A significantly higher proportion of Pyrenochaetopsis and lower relative abundance of Sordariomycetes were observed in the CFM group compared to the controls. Compared to CF and non-fertilized control (CK), CFO and CFS led to higher species richness (P < 0.05), while CFM led to a less uniform fungal community, indicated by lower Shannon and higher Simpson diversity indices (P < 0.05). Pearson’s correlation and redundancy analysis suggested that fertilizations primarily influenced the fungal community by altering the soil nutrient conditions, among which soil organic carbon and total phosphorus significantly correlated with the fungal diversity and community composition (P < 0.05). Notably, FUNGuild annotation suggested that while other treatments showed no significant effect on the fungal trophic modes, CFM strongly increased the abundance of saprotrophic fungi by more than 30% (P < 0.05), thus preventing the prevalence of potential pathotypes and symbionts. The results suggest that the type of organic fertilizers is essential to the long-term effects of organic application on the fungal community, and the animal-origin manure seems to be a better choice than plant-origin materials in continuous cropping tobacco fields.